Study of antibiotic susceptibility pattern of the isolated organisms in otitis media - Ujwala A Lokhande; Suresh L Akulwar; Lokhande, Annasaheb (Asian Journal of Medical Sciences, 2024)
Background: Otitis media (OM) encompasses a spectrum of inflammatory conditions affecting the middle ear, contributing significantly to health-care visits and prescriptions. Complications arising from OM frequently result in avoidable hearing loss, particularly in developing nations. Aims and Objectives: This study aims to ascertain the bacterial profile and antimicrobial susceptibility pattern of ear infections characterized by ear discharge complaints. Materials and Methods: The present study was conducted in the microbiology department of a tertiary care hospital over a 2-year period. The study involved 581 samples diagnosed with OM. Trained nurses collected pertinent patient information, while both nurses and an ENT doctor collected samples during specimen collection, utilizing an otoscope and headlight. Thorough documentation of relevant history and physical examinations accompanied the meticulous collection of ear discharge. Results: Culture-positive samples accounted for 96.39% (560 samples), with no growth observed in 3.61% (21 samples). Gram staining revealed 570 positive samples. Of the 581 OM samples, aerobes were isolated from 73.67% and anaerobes from 51.64%. The total isolates numbered 845, with 61.54% being aerobic and 38.46% anaerobic. Among the bacterial isolates, gram-negative bacteria slightly exceeded gram-positive bacteria, constituting 60.57% and 39.42%, respectively. Conclusion: In conclusion, the isolated aerobes and anaerobes shed light on the prevalent organisms in our region causing OM. The antibiotic sensitivity analysis conducted in this study emphasizes the identification of drugs suitable for the earliest treatment of OM.